Conservative management of traumatic brachial plexus injury: a case report - Mishra, Simran A.; Gaikwad, Stuti N.; Ganvir, Suvarna S. (International Journal of Research in Medical Sciences, 2024)
Brachial plexus injury (BPI) is one of the devastating conditions for patients, which has a negative impact on patients' quality of life. It renders patients with an inability to achieve functional independence. With advancements in surgeries and rehabilitation, improvement in these domains is possible. This case report describes the rehabilitation of a 28-year-old male patient. Being a driver by occupation and the only earning member in the family, upper limb function was essential for functional independence and resume work. After examination, problems were identified, goals were set, and intervention was planned. The patient took 2 months of inpatient rehabilitation six days a week. After completion of treatment, the patient was independent in basic and instrumental activities of daily living. The study concludes that structured, evidence-based physiotherapy treatment is effective in achieving functional independence and reducing disability in patients with traumatic BPI.